2022
DOI: 10.3390/biom12101383
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Permeable Channels Cooperation for Rheumatoid Arthritis: Therapeutic Opportunities

Abstract: Rheumatoid arthritis is a common autoimmune disease that results from the deposition of antibodies–autoantigens in the joints, leading to long-lasting inflammation. The main features of RA include cartilage damage, synovial invasion and flare-ups of intra-articular inflammation, and these pathological processes significantly reduce patients’ quality of life. To date, there is still no drug target that can act in rheumatoid arthritis. Therefore, the search for novel drug targets has become urgent. Due to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…In particular, following the protocol reported in the literature [29], 11-azido-3,6,9-trioxaundecan-1-amine 3 was prepared by the reaction of 2-(2-(2-(2-(2-azidoethoxy)ethoxy)ethoxy)ethyl)isoindoline-1,3-dione 2 in ethanol with hydrazine monohydrate by Gabriel synthesis. The structure of 3 was determined by 1 H-, 13 C-NMR, and DEPT-135 spectra (Supplementary Materials, Figures S1-S3). 1) that are important for its biological activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, following the protocol reported in the literature [29], 11-azido-3,6,9-trioxaundecan-1-amine 3 was prepared by the reaction of 2-(2-(2-(2-(2-azidoethoxy)ethoxy)ethoxy)ethyl)isoindoline-1,3-dione 2 in ethanol with hydrazine monohydrate by Gabriel synthesis. The structure of 3 was determined by 1 H-, 13 C-NMR, and DEPT-135 spectra (Supplementary Materials, Figures S1-S3). 1) that are important for its biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Heteronuclear single quantum coherence spectroscopy (HSQC), correlation spectroscopy ( 1 H-1 H-COSY), and distortionless enhancement by polarization transfer (DEPT-135, DEPT-90, and DEPT-45) were also used to assign 13 C signals of compound 4, as shown in Table S1 (see Supplementary Materials for 2D spectra, Figures S6-S10). The 13 C-NMR spectrum of 4 exhibited 37 carbon signals were classified by DEPT experiments as six methyl groups, fifteen methylene, four methines, and twelve quaternary carbons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the vanilloid subfamily of transient receptor potential vanilloid channels have received attention in OA studies . Among them, transient receptor potential vanilloid 4 (TRPV4) plays a crucial role in initiating [Ca 2+ ] i signaling in chondrocytes and is involved in the regulation of ECM biosynthesis . It has been found that the use of a TRPV4 agonist (GSK101) leads to an increase in type II collagen (Col-II) and glycosaminoglycans (GAG) in cartilage .…”
Section: Introductionmentioning
confidence: 99%